Disparities in Human Papillomavirus Vaccine Completion Rates Among Females in an Integrated Health Care System. Issue 3 (September 2018) - Freeman, Alexandra (Jana) H.; Gamboa, Cristina; Darbinian, Jeanne A.; Littell, Ramey D.; Torrente, Sandra
Abstract : OBJECTIVE: To estimate the rate of human papillomavirus (HPV) vaccine completion by race and ethnicity. METHODS: In this retrospective cohort study, we analyzed females aged 11–26 years who initiated HPV vaccination from 2008 through 2012 in a community-based health care system in California. Vaccine completion was defined as having received at least three injections. Demographic data including age, race, ethnicity, and language preferences were obtained. Among Hispanic patients, acculturation was categorized as low or high using written and spoken Spanish vs English language as a proxy. Age groups were defined as younger adolescents (11–14 years), teens (15–17 years), and young adults (18–26 years). Bivariate analyses using χ 2 tests and age-adjusted logistic regression were performed. RESULTS: Among 102, 052 females who initiated HPV vaccination, a total of 41, 847 (41%) completed the series. Younger adolescents had the highest completion rates (43.4%, P <.001) vs teens and young adults (37.4% and 38.0%, respectively). By race and ethnicity, Asian patients had the highest completion rates (49.5%, 95% CI 48.8–50.2), and the lowest rates were seen among black and Hispanic patients (28.7% [95% CI 27.8–29.6] and 38.9% [95% CI 38.3–39.5], respectively). Among Hispanic patients, the adjusted odds for vaccine completion was 1.2-fold higher for the low acculturated vs the highly acculturated group (adjusted odds ratio 1.23 [95% CI 1.16–1.31]). CONCLUSION: More than half of the females who initiated HPV vaccination did not complete the series, and black and Hispanic patients were least likely to have completed the series. Among Hispanic patients, the highest acculturated group had the lowest completion rate. These disparities emphasize the need for cancer prevention across all racial and ethnic groups. Abstract : Among a diverse group of insured females, low rates of human papillomavirus vaccination series completion were demonstrated; these rates varied by race and ethnicity.